Clinical Supervision by the Principal in an Effort to Improve the Performance and Effectiveness of Sociology Learning at SMAN 1 Menjalin - Yakobus, Yakobus; Bahari, Yohanes; Rustiyarso, Rustiyarso (Universitas Tanjungpura, 2024)
This thesis is entitledTeachers and the Effectiveness of Sociology Learning. The approach used in this research is a qualitative approach with a descriptive research type. Researchers explore the phenomena that occur in the field, then describe in the form of words and sentences. The methods used by researchers in collecting data are observation, interviews, and documentation. The results of research conducted in the field show that clinical supervision in improving teacher performance has shown good results. Although there are some drawbacks. Clinical supervision atSMA Negeri 1 Menjalin is more dependent on teacher readiness. The supervisor who supervises the teachers is the Principal of SMA Negeri 1 Menjalin. Clinical supervision at SMAN 1 Menjalin has several stages including initial preparation, initial meeting, observation. Teachers at SMA Negeri 1 Menjalin have met professional teacher standard switch have fulfilled four competencies including pedagogic competence, personal competence, professional competence and social competence. In improving these competencies, especially for the new teachers in SMAN 1 Menjalin, one way is through clinical supervision. The improvement felt by teachers who have carried out clinical supervision is increased performance and increased learning effectiveness, which can be seen from the very varied methods used, being able to manage classes well, being able to know and understand the character of each student well and being able to make participants students are active in learning.